Level of Early Childhood Education (PAUD) Teachers' Knowledge on Developing Holistic Assessment Rubrics Using the Rasch Model - Juairiyah, Juairiyah; Yudha, Rivo Panji (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
This research addresses the level of knowledge of PAUD teachers regarding the preparation of holistic assessment rubrics in South Arut District. The purpose of this study was to analyze the level of knowledge among PAUD teachers about developing holistic assessment rubrics in South Arut District. This study is a quantitative descriptive research. The method used is a survey. The subjects of this study were 65 PAUD teachers from South Arut District. The instrument used in this study was a true-false choice test. Data analysis was performed using quantitative descriptive analysis, presented in percentage form and analyzed with the Rasch model. The Rasch model employs probability principles for each available option, whereas classical test theory focuses on the total score from exams or questionnaires. The results showed that the level of knowledge of PAUD teachers regarding the preparation of holistic assessment rubrics in South Arut District was categorized as "low" for 47.7% (31 teachers), "medium" for 38.4% (25 teachers), and "high" for 13.9% (9 teachers). Based on the average score of 20.78, the level of knowledge among PAUD teachers about the preparation of holistic assessment rubrics in South Arut District falls into the "medium" category.